Biodiversity credits: a new currency to support nature conservation? - Schwerdtner Manez, Kathleen; Clifton, Julian (Oryx, 2025)
Biodiversity credits are increasingly being promoted as an innovative tool for closing the biodiversity finance gap. A growing number of providers are offering biodiversity credits, either linked to carbon credits or as a new asset class in their own right. However, there are also warnings that they could become a double-edged sword for conservation and distract governments from their financial responsibilities agreed in the Global Biodiversity Framework. Biodiversity credits differ from other environmental policy instruments in that they offer a non-offsetting way of financing conservation and restoration activities. Well-designed credit schemes can therefore make a significant contribution to real net biodiversity gains. But to realize their full potential, biodiversity credits need to be based on a common methodology, broaden their focus to include marine areas, and respect the rights of local and Indigenous communities. Benefit sharing and embedding in regulatory approaches will be critical to their success.